Research on migration on Slovenian media - Smrdelj, Rok (Annales. Series historia et sociologia, 2021)
The article presents the results of the first systematic literature review on migration in Slovenian media from the perspective of the hybrid media system. The mass media coverage of refugees and migrants is determined by the process of construction of the "other" in the Slovenian society. Stereotypical negative reporting prevails, portraying refugees and migrants as a security and cultural threat. The social media research notes the prevalence of an extremely xenophobic and racist discourse tacitly supported by the political elite and serving as a legitimisation for the government’s security policy.
Keywords: analiza diskurza; begunci; begunske krize; crisis; družbeni mediji; hybrid media systems; mass media; migranti; migrants; množični mediji; refugees; Slovenija; social media